Effects of antioxidants on physicochemical properties and odorants in heat processed beef flavor and their antioxidant activity under different storage conditions - Zhang, Zeyu; Meng, Fanyu; Wang, Bei; Cao, Yanping (Frontiers in Nutrition, 2022)
Heat processed beef flavor (HPBF) is a common thermal process flavoring, whose flavor properties can be affected by lipid oxidation during storage. Addition of antioxidants is an option to avoid the changes of HPBF induced by lipid oxidation. In this study, the effects of three antioxidants, tert-butylhydroquinone (TBHQ), tea polyphenol (TP) and L-ascorbyl palmitate (L-AP), on volatile components, physicochemical properties and antioxidant activities of HPBF were studied over 168 days at different temperatures (4 °C, 20 °C, and 50 °C). Although all three antioxidants had little effect on browning, acidity, water activity and secondary lipid oxidation products, L-AP and TBHQ showed greater capabilities to prevent the formation of primary lipid oxidation products than TP. According to the results of oxidation reduction potential and DPPH radical scavenging experiments, TBHQ had better antioxidant ability compared to L-AP and TP during the storage. Of note, TBHQ affected the flavor profiles of HPBF, mainly on volatile odorants produced by lipid degradation. TBHQ could mitigate the development of unfavorable odorants. This study indicated TBHQ would enhance lipid oxidation stability and maintain physicochemical properties and flavor profiles of HPBF during storage. It suggested that TBHQ could be applied as an alternative additive to improve the quality of HPBF related thermal process flavorings.